Cost benefit analysis of intralesional injections in keloids using Luer lock and non-locking syringes - Phadnis, Amit Prabhakar; Shinde, Sumedha; Kale, Sachin; Vatkar, Arvind; Pol, Arindaam Arjunrao; Mandal, Shobhan; Verma, Ashmit; Das, Sonali; Kale, Sachiti Sachin (International Journal of Research in Orthopaedics, 2024)
Background: For keloid scarring, intralesional corticosteroid injections continue to be the most often utilised first therapeutic option. This is a common procedure done on an outpatient basis by surgeons and orthopaedists. Luer lock syringes which lock the needle with syringe prevent any leakage or spillage of drug while pushing it near the keloid compared to normal syringes. Methods: We intend to do a cost benefit analysis based on the retrospective data of intralesional steroid injections done by the authors (AP and SK) in their private practice. Results: The time between 2021 to 2022, 200 injection data was retrieved, 100 each using non locking syringes and Luer lock syringes. The spillage rate with non-Luer lock syringes was 14%. Conclusions: We found that luer lock syringes prove to be cost effective after giving more than 200 injections in keloids than non-locking syringes.